Mothers' Knowledge about the Reproductive Health Needs of their Adolescent Girls - Zaman, B; Shampa, RM; Rahman, MA (Journal of Armed Forces Medical College, Bangladesh, 2011)
Introduction: Adolescent is an important segment of life while a child undergoes biological transformation. Objective: The study was conducted to assess the level of knowledge of mothers about reproductive health needs of their adolescent girls. Methods: This descriptive cross sectional study was conducted on the mothers having adolescent girls. Data was collected by face to face interview with a semi structured questionnaire and analyzed with SPSS. The knowledge of mothers was assessed by Likert scale. Place of study: The study was conducted at 5 schools of Dhaka city on 118 respondents over a period of four months. Results: It was revealed from the findings that among 118 mothers the mean age of respondents were 40.71 years with standard deviation ± 3.707 years. Majority (70%) of respondents were undergraduate qualified and rest were post graduats. Among the respondents, 64% of mothers did not want to provide information on reproductive health to their daughters. Seventy two percent of the respondents had average knowledge about puberty. Among the respondents, 47% had average knowledge regarding adolescent reproductive health problems and 77% of respondents had average knowledge about safe motherhood. Regarding the complication of unsafe abortion, 73% had average knowledge and 70% had average knowledge about consequence of early pregnancy. Fifty seven percent of the respondents had good knowledge about Sexually Transmitted Diseases. Sixty one percent of the respondents had good knowledge regarding the high risk behaviour of the adolescents. Significant statistical association was found between knowledge and education, knowledge and occupation, and knowledge and source of information of reproductive health (p<0.05). Conclusion: The study findings may be helpful for baseline information and would be beneficial to the policymakers and programme planners to sophisticate further strategy to increase mothers' knowledge about the reproductive health needs of their adolescent girls. Key words: Knowledge; adolescent; reproductive health needs DOI: 10.3329/jafmc.v6i2.7266 JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.9-12